2012
DOI: 10.1177/1753944712468628
|View full text |Cite
|
Sign up to set email alerts
|

The new patent foramen ovale occluder FIGULLA in complex septal anatomy: a case series

Abstract: Background: The appropriate treatment strategy for secondary stroke prevention in patients with cryptogenic stroke and patent foramen ovale (PFO) remains challenging. The aim of this study was to describe a case series of patients with PFO and complex septal anatomy who underwent percutaneous correction using a FIGULLA (Occlutech®) septal occluder (FSO). Patients: Ten consecutive patients (6 females, 4 males, mean age 41.6 ± 16.0 years, range 17-52 years; Group 1) with cryptogenetic stroke and/or transient cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Device closure was successful in only 87% of cases, which is similar to previous device closure studies with the STARFlex® device ( 52 ), but lower than that reported for other PFO closure devices ( 53 56 ). AF and major vascular complications were significantly higher in the device group, although the latter had no further implications for the patients, which was confirmed in other trials ( 57 , 58 ). The population in the CLOSURE I trial had several atherosclerotic risk factors, including increased body mass index, diabetes, hypertension, and history of ischemic heart disease predicting recurrent ischemic neurologic events; however, a diagnosis of AF after trial enrollment portended the greatest risk of recurrent events ( 59 ).…”
Section: Discussionsupporting
confidence: 79%
“…Device closure was successful in only 87% of cases, which is similar to previous device closure studies with the STARFlex® device ( 52 ), but lower than that reported for other PFO closure devices ( 53 56 ). AF and major vascular complications were significantly higher in the device group, although the latter had no further implications for the patients, which was confirmed in other trials ( 57 , 58 ). The population in the CLOSURE I trial had several atherosclerotic risk factors, including increased body mass index, diabetes, hypertension, and history of ischemic heart disease predicting recurrent ischemic neurologic events; however, a diagnosis of AF after trial enrollment portended the greatest risk of recurrent events ( 59 ).…”
Section: Discussionsupporting
confidence: 79%
“…Longer monitoring ideally for at least 72 H should be recommended. The incidence of AF/Flutter, 4.6% in our population, has been reported between 0.4-6.6% [1][2][3][4]6,7,9,[11][12][13][14][15][16][17][18]. Trabattoni has mentioned more supraventricular arrhythmias with Amplatzer versus Figulla but difference was not significant concerning paroxysmal AF [16], as similarly noted in the present study.…”
Section: Pfo Closure Drawbackssupporting
confidence: 75%
“…Both occluders achieved good results in terms of procedural success with a low rate of complication and a high rate of full occlusion. In fact, no inferiority of Occlutech devices compared to the Amplatzer devices could be established, as already noted [5,9,13,16]. Both devices are effective and safe for transcatheter PFO occlusion.…”
Section: Comparison Between Amplatzer and Occlutech Pfo Devicesmentioning
confidence: 83%
See 1 more Smart Citation
“…Few studies on PFO closure were performed using the Occlutech Figulla ® devices, and to our knowledge no reports on the third generation Figulla ® Flex II PFO Occluder are available [15, 18–20, 2224]. …”
Section: Discussionmentioning
confidence: 99%